2020
DOI: 10.1021/acs.jmedchem.0c01775
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Potent Dual Inhibitor of Acetylcholinesterase and Butyrylcholinesterase with Antioxidant Activity that Alleviates Alzheimer-like Pathology in Old APP/PS1 Mice

Abstract: The combination of the scaffolds of the cholinesterase inhibitor huprine Y and the antioxidant capsaicin results in compounds with nanomolar potencies toward human acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) that retain or improve the antioxidant properties of capsaicin. Crystal structures of their complexes with AChE and BChE revealed the molecular basis for their high potency. Brain penetration was confirmed by biodistribution studies in C57BL6 mice, with one compound (5i) displaying better … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 97 publications
(166 reference statements)
1
44
0
Order By: Relevance
“…Then, in the next plot ( Figure 1C ), we correlated both parameters to determine the strength of synaptic transmission per activated axon during each stimulus intensity. We adjusted to linear regressions the correlations in female and male degus ( R 2 value on top of the graph); then, we compared both regressions using ANCOVA analysis as previously shown ( Cisternas et al, 2019 ; Rivera et al, 2020 ; Viayna et al, 2021 ). Young female and male degus showed significantly different intercepts [ F (1 , 15) = 39.56, p < 0.001] but not different slopes ( p = 0.07).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, in the next plot ( Figure 1C ), we correlated both parameters to determine the strength of synaptic transmission per activated axon during each stimulus intensity. We adjusted to linear regressions the correlations in female and male degus ( R 2 value on top of the graph); then, we compared both regressions using ANCOVA analysis as previously shown ( Cisternas et al, 2019 ; Rivera et al, 2020 ; Viayna et al, 2021 ). Young female and male degus showed significantly different intercepts [ F (1 , 15) = 39.56, p < 0.001] but not different slopes ( p = 0.07).…”
Section: Resultsmentioning
confidence: 99%
“…The correlation between FV amplitude and the fEPSP slopes is a functional measurement and indicates when synaptic transmission is truncated or less functional. Using this technique, we demonstrated the effectiveness of natural compounds or drugs acting on the presynaptic compartment to improve its efficacy ( Cisternas et al, 2019 ; Viayna et al, 2021 ), and in the case of degus, we found that these parameters change by stressful conditions ( Rivera et al, 2020 ). The reason why, during the aging process of degus, the synaptic transmission is less efficient is unknown.…”
Section: Discussionmentioning
confidence: 99%
“… 38 This makes inhibition of BChE another activity of interest for AD treatment. 39 , 40 Like 6-chlorotacrine and huprine Y, all the hybrids showed submicromolar potencies toward human BChE (hBChE), with hybrid 12c standing out by its potency (IC 50 179 nM) 3-fold higher than that of the parent 6-chlorotacrine ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“… 50 , 51 We administered 12c orally to SAMP8 mice daily during 4 weeks at a dose of 2 mg kg –1 , a dosing regimen that had been successfully applied to other classes of multitarget agents developed in our group. 10 , 40 After 4 weeks of oral administration of this low dose of 12c (2 mg kg –1 day –1 ), it significantly ameliorated short-term and long-term working memory in treated SAMP8 mice compared with vehicle-treated mice ( Figure 5 A), as evidenced by a greatly increased discrimination index (DI), a measure of the ability of mice to differentiate between a known and a new object, when using the novel object recognition test (NORT). Because both 12c -treated and control mice had spent the same time exploring the two objects during the familiarization phase of the NORT test ( Figure S7 of the Supporting Information), the observed increase in the DI in treated mice must unambiguously result from a cognition enhancing effect by 12c .…”
Section: Resultsmentioning
confidence: 99%
“…The binding energy of MTDLs towards BChE is shown in Table S3 and the binding mode of the MTDLs at the active site gorge of BChE is shown in Figure S6 . There is substantial evidence suggesting that BChE plays an important role in regulating ACh levels in the later stages of AD [101] , [102] , [103] , [104] , [105] . Hence the inhibition of BChE is also highly desirable in addition to AChE inhibitory activity and compound 208 has displayed comparable inhibitory potency towards both AChE and BChE.…”
Section: Discussionmentioning
confidence: 99%